Evaluation of Hypertension and Renal Function in Preeclamptic Women: A Follow-Up Study at 6th Week of Postpartum - Ebru Ayguler; Gokce Anik Ilhan (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVES: Chronic hypertension stands as the primary contributing factor for cardiovascular ailments among women who have experienced preeclampsia. The purpose of this research is to examine how often preeclamptic symptoms persist at the postpartum 6th week.